2020
DOI: 10.1074/jbc.ra120.012587
|View full text |Cite
|
Sign up to set email alerts
|

Truncation of Tau selectively facilitates its pathological activities

Abstract: Neurofibrillary tangles of abnormally hyperphosphorylated tau is a hallmark of Alzheimer’s disease (AD) and related tauopathies. Tau is truncated at multiple sites by various proteases in AD brain. While many studies have reported the effect of truncation on the aggregation of tau, these studies mostly employed highly artificial conditions, using heparin sulfate or arachidonic acid to induce aggregation. Here, we report for the first time the pathological activities of various truncations of tau, including sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
94
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 83 publications
3
94
0
Order By: Relevance
“…We observed that deletion of the first 150 or 230 residues of the tau protein increased its self-aggregation, site-specific phosphorylation, and binding to and aggregation seeded by AD O-tau, while the first 50 residues deletion did not have those effects [70] . Deletion of the last 50 residues regulated the tau site-specific phosphorylation and promoted tau self-aggregation, which could be seized and seeded to aggregation by AD O-tau, while the last 20 residues deletion did not show significant effects [70] . Among all the truncated forms, Tau 151-391 was the most pathologically active.…”
Section: Tau Aggregationmentioning
confidence: 72%
See 4 more Smart Citations
“…We observed that deletion of the first 150 or 230 residues of the tau protein increased its self-aggregation, site-specific phosphorylation, and binding to and aggregation seeded by AD O-tau, while the first 50 residues deletion did not have those effects [70] . Deletion of the last 50 residues regulated the tau site-specific phosphorylation and promoted tau self-aggregation, which could be seized and seeded to aggregation by AD O-tau, while the last 20 residues deletion did not show significant effects [70] . Among all the truncated forms, Tau 151-391 was the most pathologically active.…”
Section: Tau Aggregationmentioning
confidence: 72%
“…Truncated tau is more likely to aggregate than full-length tau [62,68,69] . We recently reported that several tau truncations modulate specific sites of phosphorylation, increase tau selfaggregation, and promote the binding to oligomeric tau from AD brain (AD O-tau) and aggregation seeded by AD O-tau [70] . Among all the truncated forms, Tau151-391 causes the most serious pathological disorders and the most potent aggregation effects templated by AD O-tau in cultured cells in vitro [70] .…”
Section: Tau Truncationmentioning
confidence: 99%
See 3 more Smart Citations